Design and Realization of Metamaterial Antenna for Enhancement of Antenna Parameters in 5G Frequency - Daniel Christian Sianipar; Lutfianne Rafasari; Harfan Hian Ryanu; Bambang Setia Nugroho; Levy Olivia Nur (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2023)
Technological advancements, particularly in telecommunications, are accelerating. The speed of which data is sent and received is a critical demand in the rapidly expanding telecommunications sector. Fifth - generation (5G) technology necessitates the use of antenna that can effectively send and receive data. This study examines the design and realization of a microstrip antenna that operates at 3.5 GHz utilizing Electromagnetic Band Gap (EBG). The usage of an EBG can optimize antenna quality and dimensions. Based on the simulation results, the original antenna without EBG obtained S11 of -30.76 dB with a Gain of 2.653 dBi at 3.5 GHz. By adding the EBG structure with 4 x 4 configuration, the simulation results show a better S11 of -40.021dB and a higher Gain of 4.229 dBi, at a distance of 5 mm between the antenna and the EBG structure. For the measurement results, this antenna obtained S11 of -33.088 dB with a Gain of 4.3 dBi. In addition, there is a change in the radiation pattern between the Regular Antenna and the Antenna with EBG. In the antenna radiation pattern with EBG the current direction is reflected in phase and result in constructive reflection. Based on the parameters obtained from measurements and simulations, the antenna has achieved the target specification and can be used at a frequency of 3.5 GHz.